Incidence of the persistent median artery of the forearm in Myanmar adults - Aung, Htar Htar; Than, Thitsar Aye Maung (Japanese Association of Anatomists, 2009)
The median artery formed one of the main routes of blood supply to the forearm and hand in the embryo until 8th week of gestation. In the present study, 120 forearms were dissected. Median artery persisted in 72 forearms (60%), statistically frequent among male individuals, occurring bilaterally more often than unilaterally. The two patterns, the palmar (8.33%) and the antebrachial (51.67%) were found. The origin of the median artery was directly from the ulnar artery (50%), common interosseous artery (37.5%) and anterior interosseous artery (12.5%). In antebrachial type, it terminated in the proximal third (6.45%), middle third (37.09%) and in the distal third (56.46%). In palmar type, it entered the carpel tunnel deep to the flexor retinaculum medial to the median nerve and terminated by forming 1st and 2nd common palmar digital arteries or by joining superficial palmar arch. This study confirms that persistence of the median artery is not uncommon.